Dielectric properties of P3HT/CSA composites for energy storage applications - Uludag, Cem; Alveroglu, Esra; Koc, Kenan; Karabul, Yasar; Kilic, Mehmet; Ozdemir, Zeynep Guven (ELSEVIER, 2022)
This study has been focused on preparing Poly (3-hexylthiophene-2,5-diyl)/Camphor Sulfonic Acid (P3HT/CSA) composites in the bulk and studying their frequency-dependent electrical properties including complex permittivity, tangent loss, complex electrical modulus, impedance, and conductivity for revealing the energy storage potential of the samples. While the structural characterizations of the samples have been realized by Fourier Transformed Infrared (FT-IR) spectroscopy and Scanning Electron Microscope (SEM) images, electrical measurements have been performed by using an impedance analyzer between 20 Hz and 10 MHz. The complex permittivity analysis of the samples has uncovered that the CSA supplement has a positive effect on increasing both the energy storage ability and conductivity of P3HT. Especially, the fact that the composite containing 0.011 M CSA has a higher epsilon' value, lower tangent loss, and higher conductivity than all samples, making this composite attractive for many applications. Moreover, it has been determined for the first time that P3HT has a phase difference very close to -90 degrees at high frequencies (3-10 MHz) which is an indicator of supercapacitive nature of P3HT.
Keywords: Poly(3-hexylthiophene-2,5-diyl); Camphor sulfonic acid; Dielectric properties; Supercapacitive ability; Conductivity; SULFONIC-ACID; RELAXATION; OXIDE; Physics